Condiciones de vida y funcionalidad familiar en pacientes con tuberculosis en el Centro de Salud Venezuela - Sarango Morocho, Eduardo Fabricio (2019)
Tuberculosis is caused by Mycobacterium tuberculosis, a bacterium that almost always affects the lungs, it is a curable condition that can be prevented, it is one of the 10 causes of mortality in the world, more than 95% of deaths from Tuberculosis occurs in low and middle income countries. According to data from the Ministry of Public Health of 2018, it states that the city of Machala has a higher incidence of patients with this disease. The present investigation, addressed as objective to identify the living conditions and family functionality in patients with tuberculosis, for this purpose a descriptive and cross-sectional study was carried out; We worked with 30 patients from the Venezuela Health Center. The SF-12V2 questionnaire and the FF-SIL Test were applied to collect the information, which allowed us to assess the living conditions and the degree of family functionality. As results it was obtained that: the living conditions of the patients, more than 50% indicate that they have a good state of health; Regarding family functionality, 53% are dysfunctional families and 13% functional; In the relationship between living conditions and family functionality, it was determined that 13.3% of patients from functional households maintain a good state of health, while 36.7% of their health status is regular and corresponds to dysfunctional households. KEY WORDS: Mortality, Affection, Functional, Dysfunctional.